Asian American Identity and Drug Consumption: From Acculturation to Normalization - Moloney, Molly (2008)
This article analyzes the relationship between substance use and ethnic identity in the narratives of 206 young Asian Americans in a dance club/rave scene. We examine the meaning of drug use and found three types of narratives invoked to explain their drug use. The first noted difficulties arising from their Asian-American identities, the experience of culture clash and stresses associated with acculturation and Americanization. The second viewed their drug consumption as unusual among Asian Americans and saw their drug use as indicative of the degree to which they've grown apart from Asian culture and toward white/American culture. The final group saw neither their identities as Asian Americans, as drug users, nor as Asian American drug users as problematic. Drug use was a normal, accepted, and mundane part of their leisure time, not something they viewed as problematic or unusual.